Boron doped ultrastrong and ductile high-entropy alloys. (1st June 2018) - Seol, Jae Bok; Bae, Jae Wung; Li, Zhiming; Chan Han, Jong; Kim, Jung Gi; Raabe, Dierk; Kim, Hyoung Seop
Abstract: A new class of materials called high-entropy alloys (HEAs) constitutes multiple principal elements in similar compositional fractions. The equiatomic Fe20 Mn20 Cr20 Co20 Ni20 (at%) HEA shows attractive mechanical properties, particularly under cryogenic conditions. Yet, it lacks sufficient yield and ultimate tensile strengths at room temperature. To strengthen these materials, various strategies have been proposed mainly by tuning the composition of the bulk material while no efforts have been made to decorate and strengthen the grain boundaries. Here, we introduce a new HEA design approach that is based on compositionally conditioning the grain boundaries instead of the bulk. We found that as little as 30 ppm of boron doping in single-phase HEAs, more specific in an equiatomic FeMnCrCoNi and in a non-equiatomic Fe40 Mn40 Cr10 Co10 (at%), improves dramatically their mechanical properties, increasing their yield strength by more than 100% and ultimate tensile strength by ∼40% at comparable or even better ductility. Boron decorates the grain boundaries and acts twofold, through interface strengthening and grain size reduction. These effects enhance grain boundary cohesion and retard capillary driven grain coarsening, thereby qualifying boron-induced grain boundary engineering as an ideal strategy for the development of advanced HEAs. Graphical abstract: Image 1